The the Java Workshop: Learn Object-Oriented Programming and Kickstart Your Career in Software Development - Cuartielles, David; Göransson, Andreas; Foster-Johnson, Eric (Packt Publishing, Limited, 2019)
This Java book will guide you through Java development and help you build the knowledge and confidence to progress from the basics to become a skilled Java developer. All the key tools that you'll need to solve real-world problems are clearly explained and demonstrated with engaging, practical examples.